Ordinance no. 61, ch. 15, &sect - (:unkn) unknown (My University, 1892)
No person, company or corporation shall keep in store any gun or blasting powder, or other like explosive substance, in any house, shop or other place within the city of Madison, except in such place or magazine as shall have been approved by the city council of said city for that purpose; provided, that any person, company or corporation engaged in retailing powder, may keep for purpose of retail only, a quantity of gunpowder not to exceed two hundred pounds at any one time at his or their place of business, provided, further, that all powder so kept for sale, shall be kept in fire proof boxes or canisters, out of doors, remote from fires, lighted lamps, candles or gas jets, and such that can be readily removed in case of fire; and it shall be the duty of chief of police to see that dealers in powder comply with this section?
&sect
1 & 3, THE MADISON DAILY LEADER, Oct. 26, 1892, at 4 (Madison, South Dakota).
Keywords: GUNPOWDER - STORAGE